Expression of a dynamin 2 mutant associated with Charcot-Marie-Tooth disease leads to aberrant actin dynamics and lamellipodia formation. (15th August 2016) - Yamada, Hiroshi; Kobayashi, Kinue; Zhang, Yubai; Takeda, Tetsuya; Takei, Kohji
Highlights: The expression of dynamin mutants 555Δ3 and K562E decreased lamellipodia formation. The K562E mutation caused the disappearance of radially aligned actin bundles. The K562E mutation caused the appearance of F-actin clusters. Short F-actin assembled into immobile F-actin clusters in K562E-expressing cells. Abstract: Specific mutations in dynamin 2 are linked to Charcot-Marie-Tooth disease (CMT), an inherited peripheral neuropathy. However, the effects of these mutations on dynamin function, particularly in relation to the regulation of the actin cytoskeleton remain unclear. Here, selected CMT-associated dynamin mutants were expressed to examine their role in the pathogenesis of CMT in U2OS cells. Ectopic expression of the dynamin CMT mutants 555Δ3 and K562E caused an approximately 50% decrease in serum stimulation-dependent lamellipodia formation; however, only K562E caused aberrations in the actin cytoskeleton. Immunofluorescence analysis showed that the K562E mutation resulted in the disappearance of radially aligned actin bundles and the simultaneous appearance of F-actin clusters. Live-cell imaging analyses showed F-actin polymers of decreased length assembled into immobile clusters in K562E-expressing cells. The K562E dynamin mutant colocalized with the F-actin clusters, whereas its colocalization with clathrin-coated pit marker proteins was decreased. Essentially the same results were obtained using another cell line, HeLa and NG108-15 cells. The present study is the first to show the association of dynamin CMT mutations with aberrant actin dynamics and lamellipodia, which may contribute to defective endocytosis and myelination in Schwann cells in CMT.